2006
DOI: 10.1016/j.neuron.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System Controls Key Epileptogenic Circuits in the Hippocampus

Abstract: Balanced control of neuronal activity is central in maintaining function and viability of neuronal circuits. The endocannabinoid system tightly controls neuronal excitability. Here, we show that endocannabinoids directly target hippocampal glutamatergic neurons to provide protection against acute epileptiform seizures in mice. Functional CB1 cannabinoid receptors are present on glutamatergic terminals of the hippocampal formation, colocalizing with vesicular glutamate transporter 1 (VGluT1). Conditional deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
789
3
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 642 publications
(845 citation statements)
references
References 56 publications
42
789
3
4
Order By: Relevance
“…36 This finding appears particularly interesting in light of the compelling evidence that glutamatergic dysfunction can be related to psychiatric disorders (for review see Javitt 50 ). Taking recent evidence into account that CB1 receptors are, in addition to GABAergic terminals, as well prominently present on glutamatergic synapses 2,3 where they colocalize with VGLUT1 and influence glutamatergic transmission, 3 it was reasonable to hypothesize a potential dysregulation of VGLUT1 expression in CB1 À/À mice. Nevertheless, in situ hybridization of VGLUT1 mRNA in the brain revealed no alterations in CB1 À/À mice ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 This finding appears particularly interesting in light of the compelling evidence that glutamatergic dysfunction can be related to psychiatric disorders (for review see Javitt 50 ). Taking recent evidence into account that CB1 receptors are, in addition to GABAergic terminals, as well prominently present on glutamatergic synapses 2,3 where they colocalize with VGLUT1 and influence glutamatergic transmission, 3 it was reasonable to hypothesize a potential dysregulation of VGLUT1 expression in CB1 À/À mice. Nevertheless, in situ hybridization of VGLUT1 mRNA in the brain revealed no alterations in CB1 À/À mice ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…36 Furthermore, VGLUT1 has been shown to be co-expressed with CB1 receptors in glutamatergic neurons of the cortex and hippocampus. 3 Therefore, we evaluated male CB1 þ / þ and CB1 À/À mice for their VGLUT1 mRNA expression levels under basal conditions in order to assess if a downregulation of VGLUT1 coincides with the depressionlike FST phenotype in CB1 À/À mice. However, no significant genotype differences in VGLUT1 mRNA expression could be detected in the cortex or any sub-field of the dorsal or ventral hippocampus ( Figure 6; statistics not shown).…”
Section: Effects Of Sr141716 On Fst Behavior Are Specific For Cb1 Recmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, it has been hypothesised that suppression of excitation is the mode of action of the anti-convulsant effects of CBs (Blair, 2006;Hajos and Freund, 2002). This hypothesis has been supported in a study by Monory et al (Monory et al, 2006) where deletion of CB 1 receptors from glutamatergic terminals was shown to be pro-convulsant whereas the deletion of CB 1 receptors from GABAergic cells did not change seizure behaviour. Monory et al (2006) suggest that either DSI is not induced due to high pre-synaptic firing or because it is overwritten by DSE.…”
Section: Discussionmentioning
confidence: 86%